2010
DOI: 10.4097/kjae.2010.58.4.351
|View full text |Cite
|
Sign up to set email alerts
|

The change of T-wave on electrocardiogram after epinephrine test dose in spinal anesthetized adults

Abstract: BackgroundThis study evaluated the efficacy of a T-wave change after the IV administration of low dose epinephrine containing the test dose during spinal anesthesia.MethodsEighty healthy adults undergoing spinal anesthesia were enrolled in this study. The subjects were divided randomly into the following 4 groups: Group S (n = 20) received 3 ml of normal saline, group L (n = 20) received 3 ml of 1.0% lidocaine, group E5 received 3 ml of 1.0% lidocaine with epinephrine 5 µg, and group E10 received 3 ml of 1.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Lee et al [8] also reported similar results in spinal anesthetic patients. These studies suggest that monitoring T wave changes may constitute an approach for the detection of unintentional intravenous (IV) administration of epinephrinecontaining solution.…”
Section: Introductionmentioning
confidence: 53%
“…Lee et al [8] also reported similar results in spinal anesthetic patients. These studies suggest that monitoring T wave changes may constitute an approach for the detection of unintentional intravenous (IV) administration of epinephrinecontaining solution.…”
Section: Introductionmentioning
confidence: 53%
“…According to Knoll-Köhler et al [ 43 ], the injection of 20 μ g epinephrine produced a doubling of plasma epinephrine levels and an increase of HR of about 4 bpm after 5 min, which is all near to our measured values. Theoretically, an indirect mechanism of ß -receptor stimulation may be a decrease in plasma potassium values [ 50 ]. Low plasma potassium may cause T -wave flattening or inversion [ 51 ].…”
Section: Discussionmentioning
confidence: 99%